JSW Steel's Ispat acquisition (C) : the turnaround strategy - Sharma, Sunil; Mukherjee, Saral; Gupta, Parvinder (London : Indian Institute of Management, Ahmedabad, 2016)
JSW Steel has made the decision to retain Ispat, and attempt to resolve its many problems. JSW develops a comprehensive strategy to develop Ispat into a profitable subsidiary. To do this, many economic, management, and process changes had to be put into place, and JSW had to gain the confidence and support of its shareholders.
Originally Published InSharma, S., Mukherjee, S., & Gupta, P. (2016). JSW Steel's Ispat acquisition (B): The setback. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; JSW Steel Limited -- Case studies; Ispat -- Case studies; Steel industry and trade -- India -- Case studies; Consolidation and merger of corporations -- India -- Case studies